Odpowiedź :
W poniższych przykładach zostaną wykorzystane podstawowe regułu obliczeń na potęgach:
[tex]x^a\cdot x^b=x^{a+b}\\\\x^a: x^b=x^{a-b}\\\\x^a\cdot y^a=[xy]^a\\\\x^a:y^a=[x:y]^a=[\frac{x}{y}]^a\\\\(x^a)^b=x^{ab}[/tex]
przykład 1
[tex](-2,56)^3:(\frac{16}{25})^3=[-\frac{256}{100}:\frac{16}{25}]^3=[-\frac{256}{100}\cdot \frac{25}{16}]^3=[-\frac{16}{4} ]^3=[-4]^3=\boxed{-64}[/tex]
przykład 2
[tex](-0,9)^2:(\frac{3}{8} )^2=[-\frac{9}{10}:\frac{3}{8} ]^2=[-\frac{9}{10}\cdot\frac{8}{3} ]^2=[-\frac{3}{5}\c\frac{4}{1} ]^2=[-\frac{3}{5}\cdot\frac{4}{1} ]^2=[-\frac{12}{5}]^2=\frac{144}{25}=\boxed{5\frac{19}{25} }[/tex]
przykład 3
[tex](\frac{1^2}{3} )^4:(-\frac{2^7}{9} )^4=[\frac{1}{3}:(-\frac{2^7}{9} ) ]^4=[-\frac{1}{3} \cdot\frac{9}{2^7} ]^4=[-\frac{3}{2^7}]^4= [\frac{3}{2^7}]^4=\frac{3^4}{(2^7)^4} =\boxed{\frac{81}{2^{28}} }[/tex]
przykład 4
[tex]-(-27)^3\cdot(-\frac{1}{9} )^3-12^3:(-3)^3=[-(-27)\cdot(-\frac{1}{9} )]^3-[12:(-3)]^3=\\[27:(-9)]^3-[12:(-3)]^3=[-3]^3-[-4]^3=-27-(-64)=-27+64=\boxed{37}[/tex]
przykład 5
[tex](1,2)^3:12^3-(0,6)^5\cdot(-\frac{1^2}{3} )^5=[1,2:12]^3-[0,6\cdot(-\frac{1}{3} )]^5=\\[0,1]^3-[-0,6:3]^3=0,001-[-0,2]^3=0,001+0,008=\boxed{0,009}[/tex]